Preventive Measures in Aquaculture: Isolation, Application and Effects of Probiotics on Atlantic cod (Gadus morhua L.) Rearing at Early Stages - Lauzon, Hélène L. (2010)
Survival problems are encountered at early stages of intensive fish rearing and antibiotics are widely used to remedy the situation. Probiotics may provide a potential alternative method to protect larvae from opportunistic and pathogenic bacteria and promote a balanced environment. This research work was undertaken to promote survival and larval development at early stages of Atlantic cod (Gadus morhua L.) rearing. The first part of the study was designed to search for probiotics to target this critical period in cod rearing. Potential probionts were selected from the natural microbiota of cod larviculture at an experimental station in Iceland, based on several in vitro tests. Our study demonstrated that 14% of screened bacteria (n=188) had antagonistic properties towards fish pathogens. The majority of the isolates were Gram-positive (81%), belonging to Firmicutes (69.2%) and Actinobacteria (11.5%) phyla based on 16S rRNA gene sequencing. Only six (3.2%) of 188 isolates could inhibit all three pathogens tested, Vibrio anguillarum, Aeromonas salmonicida ssp. achromogenes and Aliivibrio salmonicida. Differences observed in activity intensity and spectrum among inhibitory isolates emphasise the need to develop probiotic mixtures for efficient prophylactic methods. Successively, three bacterial strains were tested in vivo as a mixture added to the rearing water from an early postfertilisation stage in the experimental cod hatchery. Two of the added bacteria (Arthrobacter bergerei isolated from an algal concentrate and Enterococcus thailandicus from cod larval rearing water) were re-isolated in larvae at the end of the experiment, contributing to increased survival, growth, vitality and microbiota control. A different microbial rotifer treatment was attempted to introduce putative probiotics during larval first-feeding but was not successful and led to high larval mortality. Further, the dominant culturable microbiota was characterised as influenced by specific treatments applied during two spawning seasons. ...